Role of Immune Inflammation in Recurrent Spontaneous Abortions - Wen X; Dong P; Liu J; Wang SJ; Li J (Dove Medical Press, 2024)
Xi Wen,1 Peng Dong,1 Jia Liu,1 Shi-Jun Wang,1 Jian Li1,2 1Department of Gynecology and Obstetrics, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People's Republic of China; 2Department of Family Planning, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing, 100010, People's Republic of ChinaCorrespondence: Jian Li, Department of Family Planning, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, No. 17 Qihe Lou, Dongcheng District, Beijing, 100010, People's Republic of China, Tel +86 13661343676, Email lijian1047@126.com Shi-Jun Wang, Department of Gynecology and Obstetrics, Xuanwu Hospital, Capital Medical University, Changchun Street, Xicheng District, Beijing, 100053, People's Republic of China, Tel +86 13601222289, Email wsj9188@126.comObjective: This study aimed to investigate the role of immune inflammation in recurrent spontaneous abortions (RSA).Methods: In this study, decidua tissues from 12 patients were collected. These included six individuals with RSA in the RSA group and six in the control group. The differences in gene and metabolite expression in the decidua of the placenta between normal pregnancies and patients with RSA were compared using transcriptomic and metabolomic analyses. The differentially expressed genes and metabolites were further analyzed through functional enrichment analysis using high-throughput sequencing technology.Results: There was a significant upregulation of genes associated with immunity and inflammation in the RSA group compared to the control group. The TNF signaling pathway was upregulated in the RSA group. Inflammatory mediators were expressed at higher levels in the RSA group, and arachidonic acid metabolism was the most significant differential metabolite set. The regulation of inflammatory mediators of transient receptor potential (TRP) channels were enriched in RSA cases. The integrated analysis of the data further suggests that the immune-inflammatory response might be an important factor in RSA. The expression levels of genes related to inflammation and hypoxia in tissues from patients with RSA were verified using quantitative reverse transcription polymerase chain reaction (qRT-PCR), and this revealed that the expression of MARK10 and TNFAIP3 genes was significantly upregulated in samples from RSA patients compared to normal tissues.Conclusion: The findings suggest a strong association between immune-related inflammation and RSA. Addressing metabolic and inflammatory aspects in patients with RSA may potentially help enhance pregnancy outcomes.Keywords: decidua tissue, immune inflammation, metabolomics, recurrent spontaneous abortion, transcriptomics